The urban sketcher : techniques for seeing and drawing on location - Holmes, Marc Taro (Cincinnati, Ohio : North Light Books, 2014)
You'll love this drawing book if: You want to learn urban sketching techniques You like to make pen and ink, watercolor, and pencil art Join the Urban Sketching movement and capture the bustle and beauty of life around you. From coffee shops to busy streets, you'll learn from author Marc Taro Holmes how easy it is to get started in urban sketching and how quickly you'll find a passion for drawing on location in the cities and villages you live and travel in. This workshop book will teach you how to draw inspiration from real life. Learn to capture not just what you see but also the energy and what it feels like to be there in the moment. With this guide you will learn what minimal supplies you need to get started, practical advice for working in the field, choosing subjects, capturing people in motion and more. Whether you are a seasoned artist or habitual doodler, The Urban Sketcher will have you out in the world sketching from the very first page. Inside The Urban Sketcher you'll find: 15 stepbystep demonstrations covering techniques for creating expressive drawings using pencil, pen and ink, and watercolor Expert tips for achieving balance of accuracy, spontaneity and speed Daily exercises and prompts for everything from improving essential skills to diverse approaches for montages, storytelling portraits, and onepage graphic novels A Word from the Author'If you work through the exercises and stepbystep demonstrations in order, using places and things found in your daily life, you'll gradually be introduced to all the essential skills of urban sketching. What's even better is that you'll be out in the world sketching from the very first day. You'll experience your city in a new light, you'll get better drawings by working first hand, and you'll bring back stories to go with them.'
Graphite: draw everything you see -- Pen & ink: expressive lines, powerful contrast -- Watercolor: bring sketches to life with color
Includes index.
Keywords: Drawing -- Technique; Watercolor painting -- Technique; City and town life in art